The literary patronage of Lodovico II Gonzaga, Marchese of Mantua 1444-1478 - Hare, Paul (Trinity College (Dublin, Ireland). Italian Department, 2010)
The scope of my research was to bring to life the figure of Lodovico Gonzaga as an erudite humanist statesman. Although he is often framed in such terms, conventional definitions such as "pupil of Vittorino da Feltre" and "prince of arms and letters" are so often read as to have no real significance. His peer and former schoolmate Federico da Montefeltro in Urbino, memorably depicted in his study by Justus of Ghent, enjoys a deserved reputation for being a genuine humanist prince. No such portrait exists for Lodovico, but his achievements as Marchese of Mantua, in terms of both enlightened government and patronage of the arts, made me suspect that such feats must have been underpinned by a profound humanist education as well as, in all probability, a genuine interest in letters.
Keywords: Italian, Ph.D.; Ph.D. Trinity College Dublin.